ChemInform Abstract: 2, 5‐Diketopiperazines as Privileged Scaffolds in Medicinal Chemistry, Peptidomimetic Chemistry and Organocatalysis. Issue 13 (March 2015) - Piarulli, Umberto; Panzeri, Silvia
Abstract Review: 124 refs.